Improving Early Childhood Interest In Learning Arabic Through Play-Based Methods - Aep Anwar; Ajeng Kharisma (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2026)
This study aimed to improve early childhood interest in learning Arabic through the implementation of play-based methods at RA AL Huda Pamulang. The research employed a Classroom Action Research (CAR) design involving 10 students aged 5–6 years. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation sheets, field notes, and documentation. Students’ learning interest was measured based on five indicators: attention, participation, enthusiasm, responsiveness, and task persistence. The results showed a significant improvement in students’ learning interest across research stages. In the pre-cycle stage, the overall percentage of learning interest was 45% (Fair category). After the implementation of play-based activities in Cycle I, the percentage increased to 68% (Good category). Further refinements in Cycle II, including storytelling, movement-based games, and structured group activities, resulted in an increase to 85% (Very Good category), exceeding the predetermined success criterion of 75%. The findings indicate that play-based learning effectively enhances motivation, engagement, and active participation in Arabic language instruction for young learners. The study concludes that integrating games, songs, role-play, and interactive storytelling into Arabic lessons creates a positive emotional learning environment that supports both linguistic development and intrinsic motivation. Therefore, play-based methods are highly recommended for early childhood Arabic education, particularly in Islamic educational settings.